LINGUISTIC SYMBOLIC STRUCTURE IN UTOPIAN TEXTS AND THE IDEAL SOCIETAL MODEL - Akmal Akramjonovich Davranov (Sciental Journals Publishing, 2026)
This article analyzes the process of creating an ideal societal model through the linguistic symbolic structure in utopian texts. The study examines the semantic, axiological, and pragmatic features of utopian discourse, as well as the mechanisms of societal model formation through linguistic means. The linguistic modeling and legitimization of the social system in the texts are elucidated through metaphorical codes, conceptual maps, and normative and evaluative units.
Keywords: Utopian text, linguistic symbolic structure, ideal societal model, discourse, metaphor, axiological field, semantic system, normativity, pragmatics.